O retorno de Katari: cultura histórica e processo de emergência política do movimento Cocalero na Bolívia (1995-2006) - Costa, Lício Romero (2010)
This work discusses the process of political emergence of the cocalero movement in Bolivia, specifically of the peasant coca growers whose production is centered in the tropical valleys of the department of Cochabamba, in the Chapare region. Assuming that the study of the cocaleros' own experiences is a key to understand the development of their identity and their making of as a subject of collective action, we analyzed the changes and reconfigurations within that broad contemporary social movement, amid the reality of direct struggles against the Bolivian neoliberal state. The experiences of the cocaleros during the 1980s, in the context of the War on Drugs held by the U.S. led them to assume, first, a defensive posture against attempts to eradicate their source of livelihood; which gradually took the form of a political project itself, based on demands of recognition of the indigenous nations from the Andes, greater political participation of popular segments and advocacy of a historical culture based on the ancestrality of their practices and worldview. The time frame of our research covers the period from 1995, year in which was founded the ASP the Asamblea por la Soberanía de los Pueblos, organization that would lead the instrumento político cocalero called MASIPSP, or Movimiento al Socialismo - Instrumento Político por la Soberanía de los Pueblos until the year 2006, when the presidential candidate for the MAS-IPSP assumed for the first time the most important political office in the country. The dissertation has as inspiration the productions and reflections of authors (writers and filmmakers) who belong to the specific regionality known as the South, which, like the Bolivian social movements, perceive Latin America and other regions of the world as places incorporated in a subordinate way to the process of hegemonic globalization finding that leads to an imminent reflection on possible prospects of sociopolitical, economic, cultural and epistemic decolonization of these regions.